2017
DOI: 10.23971/jaq.v2i1.827
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perilaku Konsumen Dan Label Halal Produk Makanan Rumah Tangga Terhadap Keputusan Konsumsi Di Palangka Raya

Abstract: Every individual has different manners for making choices, including choosing a need and desire. In the modern world of today has come a wide selection of products both local and international standards one of which is a food product. Namely food production in the country for food products imported from abroad, as well as processed food products such as cottage industries. Existing halal label on food products would have been very impact and influence for consumers, particularly Muslim consumers are encouraged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…It is also in line with the results of research by Novitasari et al (2019), which showed that there was no relationship between knowledge and the incidence of chronic energy deficiency of pregnant women (P = 0.136) (12). This is not by the results of research by Rahmaniar et al (2017) showing a relationship between the level of knowledge and the incidence of KEK in pregnant women, namely that out of 32 pregnant women who had less experience, there were six people (18.8%) who suffered from chronic energy deficiency and of 28 mothers who have sufficient knowledge 15 people (53.6%) of whom suffer from chronic energy deficiency (13).…”
Section: Discussion the Relationship Between Knowledge And Chronic En...supporting
confidence: 89%
See 1 more Smart Citation
“…It is also in line with the results of research by Novitasari et al (2019), which showed that there was no relationship between knowledge and the incidence of chronic energy deficiency of pregnant women (P = 0.136) (12). This is not by the results of research by Rahmaniar et al (2017) showing a relationship between the level of knowledge and the incidence of KEK in pregnant women, namely that out of 32 pregnant women who had less experience, there were six people (18.8%) who suffered from chronic energy deficiency and of 28 mothers who have sufficient knowledge 15 people (53.6%) of whom suffer from chronic energy deficiency (13).…”
Section: Discussion the Relationship Between Knowledge And Chronic En...supporting
confidence: 89%
“…Based on research by Rahmaniar et al (2017), there is a relationship between the level of knowledge and the incidence of chronic energy deficiency in pregnant women, namely from 32 pregnant women who have the insufficient ability, there are six people (18.8%) who suffer from chronic energy deficiency and of 28 mothers who have sufficient experience 15 people (53.6%) of whom suffer from chronic energy deficiency (5). According to research by Palimbo et al (2016), regarding the relationship between knowledge and attitudes of pregnant women to the incidence of chronic energy deficiency, it can be seen that the incidence of chronic energy deficiency is still relatively high, as much as 74.2% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Berarti gaya halal sebagai gaya hidup merambah juga pada pangan, yang dengan demikian tradisi pangan halal akan terus berkembang searah dengan jaminan produk halal bahwa setiap pangan halal kualitasnya terjamin. Jadi tren terbaru penelitian pangan halal Indonesia berdasarkan Gambar 3 (A) yang terkini antara lain lebih banyak membahas tentang sertifikasi halal (Listyoningrum and Albari 2012;Pane 2017;Rahmaniar, Farid, and Herliani 2017;Sutardi 2019). Yang dikaji juga adalah industri halal yang dikaitkan dukungan perbankan (Sungkawaningrum 2019;Tamimah, et al 2018), dan pemahaman atau pengetahuan konsumsi halal (Musthofa and Buhanudin 2021;Salima, RS, and Darsono 2018), agar sosialisasi produk halal khususnya pangan halal di tengah masyarakat perlu ditingkatkan lagi.…”
Section: (A) (B)unclassified